THE STRATEGICAL FRAMEWORKS OF THE PHYSICAL REHABILITATION IN SURGICAL TREATMENT OF THE PATIENTS WITH LOW BACK PAIN - LAZARIEVA, Olena; CIEŚLICKA, Mirosława; STANKIEWICZ, Błażej; MUSZKIETA, Radosław; PRUSIK, Krzysztof (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Aim of work was to develop strategic foundations of physical rehabilitation in the surgical treatment of patients with lumbar and sacral vertebrogenic compression syndromes. Methods are applied in our research: analysis of literature and theoretical research methods (analysis, interpretation and synthesis) of scientific and manual literature on the study. Abstraction (or idealization, or schematization) is an allocation of the essential foundations. There was an experimenting with schemes (as a development of their content, check reasonableness and practicality) during the development of concepts, practical models and physical rehabilitation programs. Materials: researching performed on the basis of analysis of an medical data of 542 patients, that treated on the base of SO “Institute of Neurosurgery named after acad. A.P. Romodanov NAMS of Ukraine” and rehabilitation department of the SO “Institute of Traumatology and Orthopedics NAMS of Ukraine”. Results: effectiveness of the surgical treatment depends on the timely, differentiated, adequate application of physical rehabilitation which should be based on the principles of continuity and duration of effects, which requires developing a plan for physical rehabilitation. A plan which developing, should be based on the results of the rehabilitation`s diagnosis and including the need for rehabilitation and the rehabilitation prognosis. Conclusions: the developed integrated assessment of rehabilitation potential and the need to determine the amount and intensity of physical rehabilitation.